Material Selection Overlay Road To Climate Change Resilient - Abdul Rohman (Universitas Muhammadiyah Semarang, 2016)
Abstract .Background of Management and maintenance of asphalt concrete roads is an important part in the retentionfunction of the road. The influence of rain and temperatures decrease the carrying capacity of the road. The problem ofhow the influence of heating and soaking the asphalt concrete mix. Objectives Knowing the value of the stability of themixture of fatigue pekerasan 60/70 pen bitumen, asphalt and bitumen emulsion polymer to a long warming and immersion. Methods Experimental laboratory methods to a comparative study with the durability of asphalt material laston aus AC-WC layer using 60/70 pen bitumen, bitumen and polymer modified asphalt emulsion and compare the value of stability after standard soaking, soaking after a short heating temperature of 850C for 2 days, soaking with long heating 850C temperature for 5 days. Results showed Optimum Asphalt Content (KAO) at the highest emulsified asphalt concrete by 9.5% with a value of 445 kg stability. Conclusion The stability value decreases with increasing soaking time.